Responsible Consumption: Developing Sustainable Habits of Living for The Future (International Journal of Scientific Research in Science and Technology, 2024)
This study looks at consumer behavior in a variety of socioeconomic circumstances with regard to sustainable consumption trends and variables. The study highlights the importance of personal beliefs, sociocultural elements, and outside influences by using a mixed-methods approach to uncover subtle patterns in consumer choices. To comprehend the intricacies of sustainable consumption, the theoretical framework incorporates socioeconomic variables, environmental psychology, and marketing methods. To collect both quantitative and qualitative data, the study makes use of questionnaires, interviews, and content analysis. The results emphasize how business sustainability activities and education play a part in influencing sustainable customer behavior. According to the research, there are still issues that need to be resolved, such as the absence of uniform sustainability criteria and more robust governmental interventions. The results highlight the significance of comprehensive approaches incorporating business, policy-driven, and educational activities for a sustainable future.